Wet-chemical synthesis of magnesium niobate nanoparticles powders - Santos, L. P. S.; Camargo, E. R.; Fabbro, M. T.; Longo, Elson [UNESP]; Leite, E. R. (Elsevier B.V., 2007)
Nanosized and highly reactive magnesium mobate (MgNb2O6) powders were successfully synthesized by a new wet-chemical method by means of the dissolution of Nb2O5 center dot 5H(2)O and in a solution of oxalic acid followed by the addition of stoichiometric amounts of magnesium carbonate. The Nb-Mg-oxalic acid solution was evaporated resulting in a dry and amorphous powder that was calcined in the temperature range from 200 to 900 degrees C for 2 h. The crystallization process from the amorphous state to the crystalline MgNb2O6 was followed by thermal analysis. The calcined powders characterized by FT-Raman spectroscopy, X-ray diffraction (XRD) and their morphology examined by high resolution scanning electron microscopy (HR-SEM). Pure MgNb2O6, free from the second phases and obtained at 800 degrees C was confirmed by a combined analysis using XRD and FT-Raman. The average diameter of the particles was calculated from the HR-SEM image as 70 urn approximately. This technique allows a better mixing of the constituent elements and thus a better reactivity of the mixture to obtain pre-reaction products with high purity at lower temperatures and reducing cost. It can offer a great advantage in the PMN-PT formation with respect to the solid-state synthesis. (c) 2006 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: MgNb2O6; columbite; magnesium niobate; low temperature synthesis; FT-Raman